Notice of the Discovery of an Inscribed Stone at Weem, near Aberfeldy, Perthshire. With Some Account of St Cuthbert's Connection with Weem (Proceedings of the Society of Antiquaries of Scotland, 1916)
The inscribed stone was discovered during grave digging in the old churchyard at Weem. The incised inscription is in two lines, separated from each other by a wide interval. The article attempts to interpret the inscription which is difficult to read and probably incomplete as a portion of the undressed stone has recently broken off. The inscription remains undated and undecipherable although a variety of possibilities are considered. The Perthshire place-name of Weem is believed to be derived from the Gaelic word uaim, a cave, there being in the face of the steep precipitous hill known as Weem Rock a cave, or rather there are two caves, one of\r them traditionally having a connection with St Cuthbert. The connection of Cuthbert with Weem rests solely on the Irish Life of that saint.